(untitled) (Dhaka University Journal of Biological Sciences, 2021)
An investigation was carried out in four designated wetlands to assess soil organic carbon (SOC) storage and evaluate soil nutrients of the northeastern Sylhet basin of Bangladesh. SOC storage was the highest in the Nikli wetland (4.1 Tg), followed by Hakaluki (4.0 Tg), Hail (2.8 Tg) and Balai wetland soils (2.6 Tg) at 100 cm depths. It is found that the total soil C storage across the medium low land (MLL) and low land (LL) sites covering the four wetlands of the Sylhet basin is about 13.5Tg. C storage across the MLL and LL sites at 100 cm depths was estimated about 5.1Tg and 8.4Tg respectively. It is found that SOC storage was higher in the low land sites in contrast to medium low land sites. The soil property varies depending on land types, soil depths and spatial distributions. Among the investigated wetland soils, Hakaluki wetland stored higher amount of SOC in the deeper soil layers whereas an inverse relationship between soil depth and SOC storage was noted for rest of the wetlands. It is apprehended that SOC storage thus gradually lessening in greater magnitude due to climate change and other anthropogenic reasons. An integrated management approach should be developed to restore the SOC sink. Dhaka Univ. J. Biol. Sci. 30(1): 115-124, 2021 (January)